Structure and magnetism of the solid solution GexFe4−xNy (0 ≤ x ≤ 1): from a ferromagnet to a spin glass. Issue 1 (9th December 2016) - Scholz, T.; Dronskowski, R.
Abstract : The experimental and theoretical study of the solid solution Ge x Fe4− x N y (0 ≤ x ≤ 1) reveals a structural transition from the cubic to the tetragonal system as well as a magnetic transition from a ferromagnet to a spin glass accompanying the increasing germanium concentration. Abstract : We present an experimental and theoretical study of the solid solution Ge x Fe4− x N y (0 ≤ x ≤ 1). A two-step ammonolytic reaction gives access to the compounds with phase-pure quality. The Ge x Fe4− x N y nitrides show a transition from an antiperovskite-like to a tetragonally distorted structure with increasing germanium concentration. Various experimental and theoretical methods evidence that the iron substitution by germanium exclusively takes place at the cubic Wyckoff position 1 a . Despite the phase transition, one observes a Vegard-type decrease of the lattice parameter over the entire compositional range. In addition, the nitrides have a limited nitrogen capacity: incorporating germanium drastically reduces the nitrogen content in the cubic structure, but increases it again in the tetragonal structure. Combined HT-XRD and TG-DSC measurements evidence that the germanium-richest nitrides are highly expanding materials. They first show a transition to a cubic structure before they decompose by releasing nitrogen. Magnetic measurements reveal that the gradual germanium incorporation is accompanied by a drastic weakening of the ferromagnetic interactions leading to a frustrated iron spin system. Ge0.97 Fe3.03 N0.56 is identified as a canonical spin glass with the characteristic parameters T g = 36.68(5) K, τ * = 10 −13.8(2) s, zν = 7.2(1) and Δ T m /( T m ·Δ lg  ω ) = 0.012.